Corporate Sustainability - Taticchi, Paolo; Carbone, Paolo; Albino, Vito.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Sustainability is one of the key issues in today$1 (Bs society, as confirmed by the increasing attention of governments, media, academia and the industry. In the context of sustainable development, businesses that are often referred to as part of the problem can become part of the solution. This book presents the state of the art of sustainability in corporations from a number of perspectives, which include: economy, finance, measurement and reporting, organizing for sustainability, green products, green buildings and IT. The individual chapters provide valuable insights for pursuing future research and define a proper research agenda for the years to come. Further, the relevance of the topics addressed makes the book essential reading for academics, practitioners, consultants and more generally, for all those interested in business evolution and sustainability. The book was written by prominent researchers from Italy, India, the USA and the UK.s
Green Economy -- Industrial Sustainability -- Carbon Emissions Management and the Financial Implications of Sustainability -- Sustainability and Business at a Crossroads: The Idea of Positive Investments in Creating Shared Value -- Integrating Sustainability in Capital Budgeting Decisions -- A Study of Consumer Attitudes and Behaviour Towards Sustainability in Bradford, UK: An Economical and Environmentally Sustainable Opportunity -- Setting and Managing Sustainability Goals -- Environmental Management Systems: Enabling Tools Towards Sustainability? -- The Green Option Matrix to Characterize Green Products and Practices: Applications to the Upholstered Furniture and the Footwear Industries -- Sustainability Measurement and Reporting: Impacts on Finance, Stakeholders Communication and Internal Measurement Practices -- Sustainable Use of IT -- The Green Building Revolution: Advancing Sustainability at Exponential Speed -- Existing Buildings' Energy Upgrade: An Economical and Environmentally Sustainable Opportunity.
Keywords: Economics; Sustainable development; Environmental economics; Business planning; Management information systems; Economics/Management Science; Non-Profit Enterprises/Corporate Social Responsibility; Organization/Planning.; Production/Logistics/Supply Chain Management; Business Information Systems; Sustainable Development; Environmental Economics